Pengaruh Penerapan E-Procurement Dan Sistem Pengendalian Internal Pemerintah Terhadap Pencegahan Fraud Pengadaan Barang/Jasa Pemerintah (Survei pada Pejabat Pengadaan di Kota Cimahi) - Immanuel Milenius Francesco; Hastuti Hastuti (Jurusan Akuntansi Politeknik Negeri Bandung, 2022)
According to the KPK corruption crime data for the years 2004 to 2020, the overall number of corruption cases in Indonesia's goods/services procurement sector were 20.8% of all corruption cases by type of case,. Implementing electronic procurement is one approach to get around this. The inadequate internal control system of the government is another element that creates a potential for fraud. The goal of this study was to ascertain the impact of putting internal controls and electronic procurement into place on preventing fraud in the Cimahi City Government's procurement of goods and services. This research uses a quantitative type research with a causality descriptive approach. The subject data and primary data sources used in this study were gathered through the distribution of questionnaires to 33 Procurement Officials at LPSE Cimahi City. The study's results demonstrated that the electronic procurement and government internal control system both significantly and positively impact fraud prevention.